Nutritional status of U.S. elite heptathletes 1997 USA track and field development project - Houtkooper, L. B.; Stream, M.; Poole, C.; Mullins, V. A.; Ayan, N. (1997)
The nutritional assessment profiles of these athletes, both during competition and at a low phase in their training cycles, indicated that most of the athletes have adequate to high intakes of calories, carbohydrate, protein, and fat, are lean, and are in good iron status. The athletes had adequate intakes of most vitamins and minerals with the exception of vitamin E which was low in the dietary intake of two athletes during competition and five athletes during training. Zinc intakes were also low for three athletes during competition and four athletes during training. All but four of the athletes had normal iron status during training, but two athletes had depleted iron stores. Nine athletes had creatine kinase levels higher than normal indicating they were probably experiencing higher than normal levels of physiological stress and muscle cell membrane damage. Educational information and individual consultation with each athlete was provided to assist the athletes in improving and maintaining their dietary and nutrient supplement intake with a goal to enhance their nutritional status. A copy of this report is provided for each athlete and her coach.